Recent hip fracture trends in Sweden and Denmark with age-period-cohort effects. Issue 1 (January 2017) - Rosengren, B.; Björk, J.; Cooper, C.; Abrahamsen, B.
Abstract Summary This study used nationwide hip fracture data from Denmark and Sweden during 1987–2010 to examine effects of (birth) cohort and period. We found that time trends, cohort, and period effects were different in the two countries. Results also indicated that hip fracture rates may increase in the not so far future. Introduction The reasons for the downturn in hip fracture rates remain largely unclear but circumstances earlier in life seem important. Methods We ascertained hip fractures in the populations ≥50 years in Denmark and Sweden in national discharge registers. Country- and sex-specific age-period-cohort (APC) effects during 1987–2010 were evaluated by log-likelihood estimates in Poisson regression models presented as incidence rate ratios (IRR). Results There were 399, 596 hip fractures in SE and 248, 773 in DK. Age-standardized hip fracture rate was stable in SE men but decreased in SE women and in DK. Combined period + cohort effects were generally stronger in SE than DK and in women than men. IRR per period ranged from 1.05 to 1.30 in SE and 0.95 to 1.21 in DK. IRR per birth cohort ranged from 1.07 to 3.13 in SE and 0.77 to 1.67 in DK. Relative period effects decreased with successive period in SE and described a convex curve in DK. Relative cohort effects increased with successive birth cohort in both countries but with lower risks for DK women and men and SE women born around the 1930s (age 75–86 years today and responsible for most hip fractures) partly explaining the recent downturn. Men and women born thereafter however seem to have a higher hip fracture risk, and we expect a reversal of the present decline in rates, with increasing hip fracture rates in both Denmark and Sweden during the upcoming decade. Conclusions Time trends, cohort, and period effects were different in SE and DK. This may reflect differences in general health as evident in known differences in life expectancy, healthcare organization, and prevention such as use of anti-osteoporosis drugs. Analyses indicate that hip fracture rates may increase in the not so far future.